Meningkatan Efektivitas Lembaga Pemasyarakatan sebagai Bagian dari Penegakan Hukum di Indonesia (International Forum of Researchers and Lecturers, 2024)
This study is entitled Improving the Effectiveness of Correctional Institutions as Part of Law Enforcement in Indonesia. The Correctional Institutions or Lapas, is an institution that is part of law enforcement in Indonesia. The purpose of the construction of the prisoner in Lapas is to ensure that the prisoners who have been released from prison remain accepted by the community and can continue to find employment. As a final part of the Criminal Justice System, the efficiency of Lapas functions and duties as a law enforcement agency is essential. The aim of this study is to further analyse the effectiveness of Lapas as part of law enforcement in Indonesia as well as attempts to enhance it if seen from existing facts. In this study, the method of writing normative or doctrinal jurisprudence with the study of library law is to study library materials such as reading and examining scientific books, e-journals of law, regulations of legislation, and various kinds of literature that have relevance to the subject and object of this research.